MOTIVASI, PENDORONG DAN PENGHAMBAT IBU RUMAH TANGGA DALAM PENGELOLAAN SAMPAH BERBASIS 3R (REUSE, REDUCE, RECYCLE) BERDASARKAN KELAS SOSIAL - Claudia Buana (Parsimonia - Jurnal Ekonomi dan Bisnis, 2016)
The objective of this research is to analyze what are the things that are considered as “motivation, drivers and obstacles” which affect housewives decision in applying the 3R’S method based on different social classes. This is qualitative research which applies the use of phenomenology method gathering 6 respondents from 3 different social classes. The result from this research show that respondents coming from mid-low social class only motivated to do reduce and reuse due to intrinsic motivation in the form of economic needs. Intrinsic motivation in the form of existence of the needs and expectations being a motivation for mid high class to perform 3R and the motivation for high socialclass to do reduce and reuse, whereas extrinsic motivation in the form of family encouragement became the motivation for mid high class to do reuse and high social class to do reduce and reuse.The driving factor in the form of a knowledge of environmental problems and the presence of creativity became a pusher formid high class to do reduce and recycle. While the experience became the driving factor over the high social class to do reuse. In general the obstacles to apply 3R’s waste management consist ofinternal and external factors. Internal factors related to the lack of awareness or knowledge to perform 3R, limitations of time and place as well as the high consumption patterns. While external factors related to the lack of awareness and support from the surrounding environment.